Glutathione deficiency in the pathogenesis of SARS-CoV-2 infection and its effects upon the host immune response in severe COVID-19 disease - Labarrere, Carlos A.; Kassab, Ghassan S. (Frontiers in Microbiology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 19 (COVID-19) has numerous risk factors leading to severe disease with high mortality rate. Oxidative stress with excessive production of reactive oxygen species (ROS) that lower glutathione (GSH) levels seems to be a common pathway associated with the high COVID-19 mortality. GSH is a unique small but powerful molecule paramount for life. It sustains adequate redox cell signaling since a physiologic level of oxidative stress is fundamental for controlling life processes via redox signaling, but excessive oxidation causes cell and tissue damage. The water-soluble GSH tripeptide (γ- L-glutamyl-L-cysteinyl-glycine) is present in the cytoplasm of all cells. GSH is at 1–10 mM concentrations in all mammalian tissues (highest concentration in liver) as the most abundant non-protein thiol that protects against excessive oxidative stress. Oxidative stress also activates the Kelch-like ECH-associated protein 1 (Keap1)-Nuclear factor erythroid 2-related factor 2 (Nrf2)-antioxidant response element (ARE) redox regulator pathway, releasing Nrf2 to regulate the expression of genes that control antioxidant, inflammatory and immune system responses, facilitating GSH activity. GSH exists in the thiol-reduced and disulfide-oxidized (GSSG) forms. Reduced GSH is the prevailing form accounting for >98% of total GSH. The concentrations of GSH and GSSG and their molar ratio are indicators of the functionality of the cell and its alteration is related to various human pathological processes including COVID-19. Oxidative stress plays a prominent role in SARS-CoV-2 infection following recognition of the viral S-protein by angiotensin converting enzyme-2 receptor and pattern recognition receptors like toll-like receptors 2 and 4, and activation of transcription factors like nuclear factor kappa B, that subsequently activate nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) expression succeeded by ROS production. GSH depletion may have a fundamental role in COVID-19 pathophysiology, host immune response and disease severity and mortality. Therapies enhancing GSH could become a cornerstone to reduce severity and fatal outcomes of COVID-19 disease and increasing GSH levels may prevent and subdue the disease. The life value of GSH makes for a paramount research field in biology and medicine and may be key against SARS-CoV-2 infection and COVID-19 disease.